2024
DOI: 10.3390/bioengineering11030203
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Bypass Surgery of In-Body Tissue Architecture-Induced Small-Diameter Biotube in a Goat Model: A Pilot Study

Tadashi Umeno,
Kazuki Mori,
Ryosuke Iwai
et al.

Abstract: Biotubes are autologous tubular tissues developed within a patient’s body through in-body tissue architecture, and they demonstrate high potential for early clinical application as a vascular replacement. In this pilot study, we used large animals to perform implantation experiments in preparation for preclinical testing of Biotube. The biological response after Biotube implantation was histologically evaluated. The designed Biotubes (length: 50 cm, internal diameter: 4 mm, and wall thickness: 0.85 mm) were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The basic structure of the moulds for fabricating iBTA-induced tissues is shown below. The moulds primarily consisted of outer cases with micropores and inner cores of several geometries [ 8 , 9 , 13 , 30 , 34 ]. Figure 1 shows a typical example of a mould (Biotube maker).…”
Section: Diverse Shaped Ibta-induced Tissuesmentioning
confidence: 99%
See 3 more Smart Citations
“…The basic structure of the moulds for fabricating iBTA-induced tissues is shown below. The moulds primarily consisted of outer cases with micropores and inner cores of several geometries [ 8 , 9 , 13 , 30 , 34 ]. Figure 1 shows a typical example of a mould (Biotube maker).…”
Section: Diverse Shaped Ibta-induced Tissuesmentioning
confidence: 99%
“…Therefore, these results will be reported in a separate study in the future. However, few histological images showed that the harvested connective tissues mainly comprised collagen produced by fibroblasts [ 3 , 4 , 7 , 9 ] and that the compact layers of collagen in the tissue were likely located in the vicinity of the surface [ 8 ]. These were not different from those of previous studies.…”
Section: Diverse Shaped Ibta-induced Tissuesmentioning
confidence: 99%
See 2 more Smart Citations